1987
DOI: 10.1016/0020-7292(87)90182-2
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy termination: Results of a community‐based study in Lagos, Nigeria

Abstract: A community survey in the Shomolu area of Lagos Nigeria showed the incidence of induced abortion to be 5.6%. Most of the abortions were carried out under medical supervision, using a combination of methods. Reasons for the abortions suggest that many were carried out on pregnancies that could have been prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…This is similar to 65% reported about two decades ago from Benin City in Southwestern Nigeria in 1986 11 but is lower than the 1987 report form Lagos (95.2%) 15 , or more recent reports from Jos and Ife (90%) 5 , Enugu in Southeastern Nigeria (81.7%) 17, among undergraduates in south-western Nigeria (87.5%) 16 , and the Nigeria Demographic and Health Survey, (NDHS) 2003 finding (78.5%) 14 . Contraceptive awareness has always been noted to be higher in the Southwestern Nigeria14 and in this study also, the Southwestern part of the country had the highest awareness rate with more people being aware in the urban (72.1%) than the rural (64.8%) areas.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is similar to 65% reported about two decades ago from Benin City in Southwestern Nigeria in 1986 11 but is lower than the 1987 report form Lagos (95.2%) 15 , or more recent reports from Jos and Ife (90%) 5 , Enugu in Southeastern Nigeria (81.7%) 17, among undergraduates in south-western Nigeria (87.5%) 16 , and the Nigeria Demographic and Health Survey, (NDHS) 2003 finding (78.5%) 14 . Contraceptive awareness has always been noted to be higher in the Southwestern Nigeria14 and in this study also, the Southwestern part of the country had the highest awareness rate with more people being aware in the urban (72.1%) than the rural (64.8%) areas.…”
Section: Discussionsupporting
confidence: 80%
“…Instructively none of the respondents in both the urban and rural areas in any of the regions attributed non-usage of contraceptive method to cost. The fear of side effects is a recurring issue in contraceptive use/non use 1,[5][6][7]9,11,12,15,16,[26][27][28][29] . Proper counselling is necessary to allay these fears for those who come forward, and inclusion of appropriate messages to address this issue during information dissemination and contraceptive awareness campaigns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 Married women also experience unwanted pregnancy, as they constituted 34.8% and 63.2% of abortion seekers in two studies respectively from Southwestern Nigeria. 2,8 It has been reported that some women use abortion as a means of child spacing instead of contraception. 9 This may be as a result of low contraceptive prevalence rates despite reported high contraceptive awareness and enlightenment drives.…”
Section: Introductionmentioning
confidence: 99%